2020
DOI: 10.1101/2020.03.04.20029538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanopore target sequencing for accurate and comprehensive detection of SARS-CoV-2 and other respiratory viruses

Abstract: 24The ongoing novel coronavirus pneumonia COVID-19 outbreak in Wuhan, China, has engendered 25 numerous cases of infection and death. COVID-19 diagnosis relies upon nucleic acid detection; 26 however, current recommended methods exhibit high false-negative rates, low sensitivity, and 27 cannot identify other respiratory virus infections, thereby resulting patient misdiagnosis and 28 impeding epidemic containment. Combining the advantages of target amplification and long-read, 29 real-time nanopore sequencing, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 35 publications
0
39
1
2
Order By: Relevance
“…Based on median and mean estimates, we have on average a mutation accumulation rate of half a dozen per patient. Although there have been data reported from single-molecule sequencing platform but they are low in coverage [39].…”
Section: Resultsmentioning
confidence: 99%
“…Based on median and mean estimates, we have on average a mutation accumulation rate of half a dozen per patient. Although there have been data reported from single-molecule sequencing platform but they are low in coverage [39].…”
Section: Resultsmentioning
confidence: 99%
“…NTS identified positive to 22 of 61 suspected COVID-19 specimens that were either negative or inconclusive by RT-PCR. Screening mutations showed that 4 of 19 throat swab samples from COVID-19 patients were found single-nucleotide mutations at seven sites [97]. These findings suggested that NTS is suitable for the identification and mutation monitoring of SARS-CoV-2 from clinical samples.…”
Section: Genomic Sequencing In Sars-cov-2mentioning
confidence: 92%
“…As of March 2020, hundreds of SARS-CoV-2 genomes were released on public databases including Global initiative on sharing all influenza data (GISAID), NCBI GenBank and China National GeneBank DataBase (CNGBdb). At present, sequencing methods of SARS-CoV-2 include metatranscriptomics sequencing [27], hybrid capture-based sequencing [96], amplicon sequencing [96], and nanopore targeted sequencing [97]. The advantages and disadvantages of SARS-CoV-2 genomic sequencing are shown in Table 1.…”
Section: Genomic Sequencing In Sars-cov-2mentioning
confidence: 99%
“…Moreover, it could identify 40 other respiratory viruses and monitor changes in virulence and transmissibility caused by viral mutations. 109 Therapeutic agents All patients should be treated in isolation. 53 Based on previous studies, drugs may be developed to inhibit cell entry.…”
Section: Diagnosis and Therapy Diagnostic Methodsmentioning
confidence: 99%